Short Communication: No Jurassic Sediments on Sumba Island? - van Gorsel, J.T. (Han) (Ikatan Ahli Geologi Indonesia, 2012)
Roggeveen (1929) described a small ammonite fragment from SW Sumba Island, provisionally identified as a Middle Jurassic species. It is associated with Inoceramus-type bivalves. The presence of Jurassic age sediments within the intensely deformed Mesozoic section of Sumba was accepted by some authors and this presence of Jurassic ammonites and bivalves was used to support the presence of Australian continental basement crust on Sumba and South Sulawesi.However, subsequent workers on the geology of Sumba have been unable to find additional fossil evidence for the presence of Jurassic sediments on Sumba; the oldest rocks that could be reliably dated are of Late Cretaceous age.Three ammonite specialists were consulted to check the identification of the ammonite illustrated from Sumba by Roggeveen (1929). They concluded that the fragment could not be reliably identified and could well be a Cretaceous species, and also suggested that the associated Inoceramus looked like Cretaceous species. There is therefore no reliable evidence for the presence of any rocks older than Late Cretaceous on Sumba, and it remains to be demonstrated whether basement of Sumba contains any Australia-derived continental material.